Giacometti, Sugimoto: en scène = Giacometti, Sugimoto: staged - Sugimoto, Hiroshi 1948-; Cohen, Françoise (Fondation-Giacometti-Institut, 2024)
In 2013, the MoMA in New York invited Hiroshi Sugimoto to photograph the masterpieces of the museum's Sculpture Garden. This commission led to the birth of the new Past Presence series. Photographing Giacometti's La Grande Femme (Tall Woman), once in broad daylight, once at dusk, Sugimoto links this duality to the fantastic that innervates Noh theatre plays. In 2024, the Giacometti Institute is exhibiting Hiroshi Sugimoto. Organized around the reconstruction of a Noh scene animated by a selection of sculptures by Giacometti, but also films, sculptures and ancient Noh masks from the photographer's collection, the exhibition highlights the proximity of the two artists' research where apparitions and reality dialogue
"Cet ouvrage est publié à l'occasion de l'exposition Giacometti, Sugimoto: en scène présentée à l'Institut Giacometti du 5 avril au 23 juin 2024."
Keywords: Giacometti, Alberto -- 1901-1966; Giacometti, Alberto -- 1901-1966 -- Große Stehende Frau III; Sugimoto, Hiroshi -- 1948-; The Museum of Modern Art -- New York, NY; Geschichte 2013; Motiv; Nō-Spiel; Rezeption; Skulpturenpark; Fotografie; Ausstellungskatalog -- Institut Giacometti -- 05.04.2024-23.06.2024 -- Paris; Bildband